The Role of Relationship Values and Trust in Improving Business Relationship Performance - Nur Aziz Sugiharto; Bheben Oscar (International Journal of Social Science and Business, 2026)
Despite the growing interest in relationship marketing, previous studies have shown inconsistent findings and limited integration of how value and trust in relationships jointly influence relationship performance, particularly in the context of emerging markets. This study aims to analyze the determination of value in business relationships by examining the influence of value and trust in relationships on relationship performance. The study involved 360 respondents representing leaders of companies or institutions involved in inter-organizational collaboration in West Java, Indonesia, who were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results of the study revealed three main findings: (1) relationship value has a positive and significant influence on trust formation (β = 0.487; p < 0.001), (2) trust significantly improves relationship performance (β = 0.632; p < 0.001), and (3) relationship value also has a direct impact on relationship performance (β = 0.281; p < 0.01). Furthermore, the findings indicate that both in a way partial or total, the relationship between variables own positive and significant influence. Trust plays an important mediating role in strengthening the relationship between relationship value and relationship performance. This finding strengthens the proposition that valuable business relationships are a function of interaction quality (relationship value), social capital (trust), and performance outcomes. This study provides a theoretical contribution by integrating relational and performance perspectives in a unified model. In the Indonesian business context, practically, these findings suggest that organizations should prioritize building trust and enhancing relationship value to achieve sustainable collaborative performance.